Abstract PS1-02-24: Physical activity level differences among Non-Hispanic White and Chinese American breast cancer survivors - C. Cao; T. Shao; A. Tsang; M. Kwa; R. Brown; L. Chen; M. Schwartz; D. Roblin; M. H. Antoni; L. Hilakivi-Clarke; G. Kowk; A. Lin; et al. (Clinical Cancer Research, 2026)
Abstract INTRODUCTION: Increased physical activity (PA) in breast cancer patients has been associated with multiple benefits including lower fatigue, depression and anxiety levels, better tolerance of treatment related side effects, and lower cancer recurrence rates (1). The American Cancer Society recommends that cancer survivors undergo at least 150-300 minutes of moderate intensity activity or 75-150 minutes of vigorous activity per week and encourages meeting or exceeding these upper limits (2). Given limited data on PA in Chinese American breast cancer survivors, this study aimed to evaluate and better quantify PA in this population. METHODS: As a part of a broader prospective cohort study investigating survivorship in Chinese American breast cancer patients compared to Non-Hispanic white (NHW) patients over a 12-month period, participants underwent a baseline phone survey administered by trained staff. All participants were women aged over 18, diagnosed with stage 0-III breast cancer within 10 years, and had completed primary surgical or medical treatment. The survey included the Global Physical Activity Questionnaire developed by World Health Organization (WHO), which was used to evaluate time spent on moderate and vigorous activity during work, travel and leisure and to calculate weekly metabolic equivalent (MET) minutes per week for each group. Group differences were evaluated using T-tests for significance. RESULTS: A total of 133 NHW and 110 Chinese American patients completed the baseline survey. The average age was 56 for Chinese Americans and 59 for NHWs, and the difference was not statistically significant. The average BMI of Chinese Americans (23.6) was statistically significantly lower than that of NHWs (25.7). Chinese Americans spent an average of 71 minutes per week on vigorous activity and 424 minutes per week on moderate activity compared to NHWs who spent an average of 179 minutes per week and 627 minutes per week, respectively. Combined, Chinese Americans averaged 2266 MET-minutes per week, while NHWs averaged 3952 MET-minutes per week, this difference was statistically significant (p = 0.0053). Additionally, for patients reporting use of a step counter, the average daily step count for Chinese Americans was 6592 compared to 8432 for NHWs. The reported average daily sedentary time for Chinese Americans (337 minutes) was not statistically different from that for NHWs (348 minutes). CONCLUSION: While both groups exceeded recommended PA minimums, Chinese American women with breast cancer self-reported significantly lower levels of PA than their NHW counterparts. Further studies should focus on the impact of this discrepancy on survivorship and possible interventions to bridge the gap between the two groups to mitigate health disparity after breast cancer treatment. KEYWORDS: breast cancer; survivorship; exercise; disparity SOURCES: (1) Le Y, Gao Z, Gomez SL, Pope Z, Dong R, Allen L, Chang MW, Wang JH. Acculturation and Adherence to Physical Activity Recommendations Among Chinese American and Non-Hispanic White Breast Cancer Survivors. J Immigr Minor Health. 2019 Feb;21(1):80-88. doi: 10.1007/s10903-018-0721-x. PMID: 29569102; PMCID: PMC6151158. (2) Rock CL, Thomson C, Gansler T, Gapstur SM, McCullough ML, Patel AV, Andrews KS, Bandera EV, Spees CK, Robien K, Hartman S, Sullivan K, Grant BL, Hamilton KK, Kushi LH, Caan BJ, Kibbe D, Black JD, Wiedt TL, McMahon C, Sloan K, Doyle C. American Cancer Society guideline for diet and physical activity for cancer prevention. CA Cancer J Clin. 2020 Jul;70(4):245-271. doi: 10.3322/caac.21591. Epub 2020 Jun 9. PMID: 32515498. Citation Format: C. Cao, T. Shao, A. Tsang, M. Kwa, R. Brown, L. Chen, M. Schwartz, D. Roblin, M. H. Antoni, L. Hilakivi-Clarke, G. Kowk, A. Lin, K. Joseph, J. X. Osorio, J. H. Wang, S. Cai. Physical activity level differences among Non-Hispanic White and Chinese American breast cancer survivors [abstract]. In: Proceedings of the San Antonio Breast Cancer Symposium 2025; 2025 Dec 9-12; San Antonio, TX. Philadelphia (PA): AACR; Clin Cancer Res 2026;32(4 Suppl):Abstract nr PS1-02-24.